2020
DOI: 10.3390/ijerph17218089
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gene–Environment Interactions on Cancer Development

Abstract: Several epidemiological and experimental studies have demonstrated that many human diseases are not only caused by specific genetic and environmental factors but also by gene–environment interactions. Although it has been widely reported that genetic polymorphisms play a critical role in human susceptibility to cancer and other chronic disease conditions, many single nucleotide polymorphisms (SNPs) are caused by somatic mutations resulting from human exposure to environmental stressors. Scientific evidence sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 105 publications
(135 reference statements)
0
34
0
Order By: Relevance
“…The complex interplay between human genes and environmental exposures significantly contributes to the etiology of cancer. Dietary pattern and nutrients intake, as well as quantity and quality of diet, are reported to play a role in cancer development [ 32 ]. It has been indicated that the risk for developing cancer varies among individuals with similar dietary intakes, which could partly be explained by genetic variation in the form of SNPs, the most common genetic variation involved in nutrient genetic heterogeneity [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The complex interplay between human genes and environmental exposures significantly contributes to the etiology of cancer. Dietary pattern and nutrients intake, as well as quantity and quality of diet, are reported to play a role in cancer development [ 32 ]. It has been indicated that the risk for developing cancer varies among individuals with similar dietary intakes, which could partly be explained by genetic variation in the form of SNPs, the most common genetic variation involved in nutrient genetic heterogeneity [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of AML is further growing in the persons with GSTM1 deletion [48]. The above-mentioned facts prove that single polymorphisms usually only have a small effect on cancer risk [49].…”
Section: Genetic Syndromesmentioning
confidence: 98%
“…It is well-established that salt induces a chronic inflammatory response [ 27 , 28 ]. Cancers are known to have multifactorial etiology [ 29 , 30 ]. The relationship between hypertension and cancer has been a considerable area of debate for the past five decades.…”
Section: Salt Induced Tumorigenesismentioning
confidence: 99%